The WtmsDW Locus on Wheat Chromosome 2B Controls Major Natural Variation for Floret Sterility Responses to Heat Stress at Booting Stage - Erena, Million F.; Lohraseb, Iman; Munoz-Santa, Isabel; Taylor, Julian D.; Emebiri, Livinus C.; Collins, Nicholas C. (Frontiers in Plant Science, 2021)
Heat stress at booting stage causes significant losses to floret fertility (grain set) and hence yield in wheat (Triticum aestivum L.), yet there is a lack of well-characterized sources of tolerance to this type of stress. Here we describe the genetic analysis of booting stage heat tolerance in a cross between the Australian varieties Drysdale (intolerant) and Waagan (tolerant), leading to the definition of a major-effect tolerance locus on the short arm of chromosome 2B, Wheat thermosensitive male sterile-2 (Wtms2). Wtms2 offsets between 44 and 65% of the losses in grain set due to heat, suggesting that it offers significant value for marker-assisted tolerance breeding. In lines lacking the Wtms2 tolerance allele, peaks in sensitivity were defined with reference to auricle distance, for various floret positions along the spike. Other (relatively minor) floret fertility response effects, including at the Rht-D1 dwarfing locus, were considered likely escape artefacts, due to their association with height and flowering time effects that might interfere with correct staging of stems for heat treatment. Heat stress increased grain set at distal floret positions in spikelets located at the top of the spike and increased the size of spikelets at the base of the spike, but these effects were offset by greater reductions in grain set at other floret positions. Potentially orthologous loci on chromosomes 1A and 1B were identified for heat response of flowering time. The potential significance of these findings for tolerance breeding and further tolerance screening is discussed.